(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Pharmacology education is integral to nursing curricula, equipping students with essential knowledge and skills for safe medication management and effective patient care. This article explores strategies for integrating pharmacology content into nursing programs, focusing on competency development and ensuring alignment with practice standards. Key themes include curriculum mapping, interdisciplinary collaboration, active learning strategies, clinical experiences, technology integration, and competency domains such as knowledge acquisition, clinical judgment, communication skills, patient safety, and ethical considerations. By incorporating these strategies, nursing educators can prepare students to navigate complex medication regimens and promote optimal patient outcomes in diverse healthcare settings.